The dominant (مجلة إحالات, 2026)
In this text that André Jarry translated from English into French, and we, in turn, translate it from French into Arabic, Roman Jakobson describes an essential term that Russian formalists wereinterested in. It is the term of the dominant that refers to the specific and main linguistic constituentof artwork in general, and the poetic work in particular. It is a constituent whose form, such as rhyme,syllabic diagram and intonation, differ on the basis of the relation that the poem establishes with otherarts, such as music, and the multiplicity of literary schools, such as romanticism and realism, and its artistic value changes, negatively and positively, from one historical period to another, and it nevertheless contributes to the domination of the aesthetic function.